Intimate partner homicide in New Zealand, 2004–2019. Risk markers, demographic patterns, and prevalence - Daly, Martin (Journal of criminology, 2024)
Intimate partner homicide (IPH) is a worldwide scourge and a topic of great interest in New Zealand, but its patterns and prevalence have not been quantified and compared to those in other comparable countries such as Australia, Canada, the United Kingdom, and the United States. Using a data set of the 187 IPH cases known to have occurred in New Zealand over 16 years, 174 of which involved current or former marriage (including de facto marriage) partners, we present analyses demonstrating the following. As in other comparable countries, a large majority of IPH victims are women, and the wife's youth, spousal age disparity, and de facto marriage are all associated with elevated risk. New Zealand is also unexceptional with respect to gross IPH rates, a very high incidence of recent marital separation as a trigger for male violence, a substantial incidence of offender suicide when the perpetrators are men but not when they are women and an overrepresentation of stepfamilies among the spousal cases. Despite frequent claims that New Zealand is exceptional in the magnitude of its intimate partner violence problem, the true picture is strikingly similar to that in other comparable countries.